RANCANG BANGUN APLIKASI SEARCH ENGINE REPOSITORY SOFTWARE DESKTOP MENGGUNAKAN TEKNIK WEB EXTRACTION - Dako Adi Ahmadi; Wamiliana Wamiliana; Wisnu Wardhana (Jurnal Komputasi, 2016)
The System Search Engine Repository Software Desktop was created with the aim for facilitating the users to get the software to be installed or used by the user. For Windows operating systems and Macintosh, the system can download and check the latest version of the software that is already available. The system created provides a freeware software for Windows and Macintosh operating systems. For Linux, the system displays and generates sources.list of Debian. In this research the system made using Extreme Programming and using web extraction techniques to extract data from website www.filehippo.com. Keywords: web scraping, search engine, extreme programming, web extraction.